Immunomodulatory Effect of Hypertonic Saline Solution in Traumatic Brain-Injured Patients and Intracranial Hypertension - Quiñones-Ossa, Gabriel A.; Shrivastava, Adesh; Perdomo, William Andres Florez; Moscote-Salazar, Luis R.; Agrawal, Amit (Indian Journal of Neurotrauma, 2020)
Traumatic brain injury (TBI) is often associated with an increase in the intracranial pressure (ICP). This increase in ICP can cross the physiological range and lead to a reduction in cerebral perfusion pressure (CPP) and the resultant cerebral blood flow (CBF). It is this reduction in the CBF that leads to the secondary damage to the neural parenchyma along with the physical axonal and neuronal damage caused by the mass effect. In certain cases, a surgical intervention may be required to either remove the mass lesion (hematoma of contusion evacuation) or provide more space to the insulted brain to expand (decompressive craniectomy). Whether or not a surgical intervention is performed, all these patients require some form of pharmaceutical antiedema agents to bring down the raised ICP. These agents have been broadly classified as colloids (e.g., mannitol, glycerol, urea) and crystalloids (e.g., hypertonic saline), and have been used since decades. Even though mannitol has been the workhorse for ICP reduction owing to its unique properties, crystalloids have been found to be the preferred agents, especially when long-term use is warranted. The safest and most widely used agent is hypertonic saline in various concentrations. Whatever be the concentration, hypertonic saline has created special interest among physicians owing to its additional property of immunomodulation and neuroprotection. In this review, we summarize and understand the various mechanism by which hypertonic saline exerts its immunomodulatory effects that helps in neuroprotection after TBI.
Keywords: saline hypertonic solutions; traumatic brain injury; immunomodulation; lymphocyte; neutrophils; intracranial pressure; intracranial pressure increase; immune system